Microstructure, fracture, electrical properties and machinability of SiC-TiNbC composites. Issue 14 (November 2017) - Fides, Martin; Hvizdoš, Pavol; Bystrický, Roman; Kovalčíková, Alexandra; Sedlák, Richard; Sedláček, Jaroslav; Džunda, Róbert
Abstract: Three SiC based composites with 30, 40 and 50% of additives (Ti and NbC with ratio of 9:16) have been prepared by hot pressing without other sintering additives. The microstructure, porosity, and chemical composition were studied using SEM/EDS. Local mechanical properties such as hardness and elastic modulus of individual components of the composite were investigated by nanoindentation. Hardness and fracture toughness of the composites were evaluated by means of Vickers macroindentation. Indentation cracks were observed and their propagation was analyzed. It was shown that the present phases were distributed uniformly. The materials with 40 wt% and 50 wt% TiNbC were almost fully dense with porosity lower than 1%. The individual constituents shown similar elasticity modulus (550–590 GPa). Indentation fracture toughness was comparable in all materials, between 2.7–3.0 MPa.m 1/2 . Cracks in SiC were mostly straight, transgranular. In other places they propagated both trans- and intergarnularly, often followed SiC/TiNbC and TiNbC/TiNbC grain boundaries. The four-point bending strength was 435 MPa for 30% TiNbC and is comparable in all materials within the error of measurement. These results suggest much lower cohesive strength of TiNbC grain boundaries. Electrical conductivity increased with increasing amount of TiNbC and in all materials was more than 1000 S/m. Consequently, all composites were EDM machinable, the surfaces of the cut were intensively oxidized.